The SLC16A11 Risk Haplotype for Type 2 Diabetes (T2D) Is Associated to Differentiated Responses in Weight Loss, and Glucose Metabolism After Treatments to Prevent T2D. (29th May 2020) - Sevilla, Magdalena; Gomez-Velasco, Donaji; Cruz-Bautista, Ivette; Lazaro-Carrera, Laura; Almeda-Valdes, Paloma; Tusie-Luna, Teresa; Manning, Alisa; Aguilar-Salinas, Carlos
Abstract: Objectives: A haplotype in SLC16A11 is associated with decreased insulin action, and risk for type 2 diabetes (T2D) in Mexicans. We aim to determine the impact of the risk haplotype on SLC16A11 on early therapeutic responses in treatments to prevent T2D. Methods: We recruited subjects with at least one prediabetes criteria according to the American Diabetes Association, and body mass index 25–45 kg/m2. Subjects were randomized in two groups: lifestyle intervention (LSI): hypocaloric diet, 25 kcal/kg of ideal weight, 45% of the total intake of carbohydrates, 30% lipids and 15% protein sources + physical activity (>150 min medium intensity per week), or LSI + metformin (750 mg prolonged release twice a day). Interventions were prescribed by standardized dietitians. The goal was to achieve >3% weight loss. We evaluated the early treatment response in a follow-up period of 12 weeks with intermediate visits each 3 weeks to reinforce knowledge and treatment goals. Evaluations (baseline and post-treatment) included an oral glucose tolerance test (OGTT), and dual-energy X-ray absorptiometry. Adherence to treatment was measured trough electronic recordings. Participants were genotyped for the risk allele rs13342232. Researchers remained blinded to the genotype results. The effects of the risk haplotype were evaluated with linear and logistic regressions adjusted by age, sex, and baseline body fat %. Results: We evaluated 61 subjects, 30 carriers, and 31 non-carriers. Most of participants (57%) achieved ≥3% weight loss. The LSI + metformin treatment increased in carriers, 2 times OR 3 IC95% (1.07 – 8.6) ( P  = 0.04) the probability to reach the ≥3% weight loss goal compared with LSI and non-carriers. In the same treatment, carriers had a greater decrease in the total and incremental area under the curve of insulin in the OGTT IC95% (−1.75 −0.11) ( P  = 0.02) compared with non-carriers and LSI. Carriers also had higher decrease in postprandial glucose compared with non-carriers regardless of treatment −12.63 + 30.38 vs 0.71 30.24 ( P  = 0.02). Conclusions: After 12 weeks of treatment, carriers with prediabetes showed a higher probability achieve weight loss and to improve insulin secretion with metformin. Regardless of the treatment, carriers were prone to improve postprandial glucose. Funding Sources: Miguel Aleman Medical Research Award.